Letecká báze na Českomoravské vysočině - Pavel Petr (Theatrum Historiae)
The signing of the Munich Pact at the end of September 1938 did not only signify the demise of the first Czechoslovak Republic, but it also brought an end to a range of policies and regulations that Czechoslovakia had adopted in the second half of the 1930s in order to prepare for a potential conflict with Nazi Germany. This preparation entailed not only the well-known construction of the fortification line along the border with Germany, but also extensive construction of new airports. After their completion, most of these airports were meant to serve the needs of the Czechoslovak Air Force. However, some of them were conceptualized and built as bases for air force units of France and the Soviet Union, then Czechoslovakia’s allies, in case of a war with Germany. The exact scope of French and Soviet intervention in any such conflict was defined by the first of several international treaties Czechoslovakia, France and the Soviet Union signed in 1935. The signing of a general treaty of alliance between Czechoslovakia and the Soviet Union then led to a multitude of mutual visits and meetings which culminated in 1937-1938 when the Czechoslo- vak Air Force was equipped with 61 modern bombers Tupolev SB-2. In exchange, the Soviets gained access to some of the modern weapon technologies developed by Škoda Plzeň. The signing of the above-mentioned treaty with the Soviet Union and the visits of representatives of the Red Army Air Force to Czechoslovakia drew severe criticism from Nazi Germany, whose Reich Ministry of Public Enlightenment and Propaganda, led by Joseph Goebbels, organized campaigns proclaiming that large airports were being built for Soviet heavy bombers on our territory. Though it is true that the information broadcast by Goebbels’s ministry was purposely manipulated in order to magnify the perceived threat to Germany, it should also be noted that airports for foreign air force units did exist on Czechoslovakia’s territory. Their construction, which was kept top secret, was approved on 22nd July 1937 by the then Chief of Staff, Army General Ludvík Krejčí. After considering a variety of alternatives, the so-called “Air Bases on the Czecho-moravian Highlands” project was selected. The project entailed the construction of airports in Pardubice, Chrudim, Hlinsko, Humpolec, Polička, Banín, and in Bystřice nad Pernštejnem, each of which was supposed to accommodate one Czechoslovak Air Force squadron (which roughly equalled an RAF wing in size). The land needed for the construction was either bought or rented. The airports in Chrudim and Pardubice were supposed to provide permanent bases for units of the Czechoslovak Air Force, albeit smaller ones during the period of peace. Although construction work was carried out intensively on all airports, only the bases in Pardubice and Chrudim had been finished and ready for operational use by September 1938. At the end of September 1938, a Soviet Air Mission, under the command of General J.V. Smuškevič, flew to Czechoslovakia. However, it is a well-known fact that Czechoslovakia accepted the Munich dictate to avoid a conflict with Germany, and the above-mentioned airports were never used by the Soviet or French air forces. Some of the airports were finished during the German occupation of Czechoslovakia and used for the needs of the Luftwaffe. The airports in Chrudim, Pardubice and Polička continue to serve their purpose until today.